ECO-FRIENDLY REPLACEMENT FOR PAPER CONSERVATION: ADHESIVES COMPRISING POTATO STARCH AND SOY FLOUR - Hashim, Nur Athmar; Ramze, Nur Miza Syakirah Muhammad; Shuhaimi, Nur Farhana; Mustafa, Nor Hanim; Zulkifle, Nor Fazura Md (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2025)
Adhesives for the preservation of paper-based heritage materials should be stable, reversible, safe for the artefact as well as effective. This study aimed to evaluate and compare the performance of natural glues derived from soy, potato, and corn flour in terms of their applicability to heritage conservation. Using A4 paper sheets of two different weights (70gsm and 100gsm), the adhesives were assessed for physicochemical and curing properties such as colour, texture, and pH; alongside curing time, bonding strength, and their long-term effects on the physical and visual integrity of the paper. Among the formulations, the potato flour-based adhesive (pH 7.40) exhibited optimal performance, showing excellent appearance, zero residue, strong and uniform adhesion, and high visual stability. In contrast, the cornflour (pH 6.32) and soy flour (pH 8.03) adhesives presented shortcomings, including non-uniform adhesion, powdery residues, and potential for discoloration. In line with the current conservation practices that prioritize sustainability and low intervention, the findings suggest that potato starch is most promising natural glue for supporting the stability of the material and ensuring long-term heritage sustainability.